Nanoscale tuning of VCAM-1 determines VLA-4-dependent melanoma cell plasticity on RGD motifs - Amschler, Katharina; Spatz, Joachim P. (Molecular cancer research, 2018)
The biophysical fine-tuning of cancer cell plasticity is crucial for tumor progression but remains largely enigmatic. Although vascular cell adhesion molecule-1 (VCAM-1/CD106) has been implicated in melanoma progression, here its presentation on endothelial cells was associated with diminished melanoma cell spreading. Using a specific nanoscale modulation of VCAM-1 (tunable from 70 to 670 ligands/μm²) next to integrin ligands (RGD motifs) in a bifunctional system, reciprocal regulation of integrin α4 (ITGA4/VLA-4/CD49d)-dependent adhesion and spreading of melanoma cells was found. As the VCAM-1/VLA-4 receptor pair facilitated adhesion, while at the same time antagonizing RGD-mediated spreading, melanoma cell morphogenesis on these bifunctional matrices was directly regulated by VCAM-1 in a dichotomic and density-dependent fashion. This was accompanied by concordant regulation of F-actin cytoskeleton remodeling, Rac1-expression, and paxillin-related adhesion formation. The novel function of VCAM-1 was corroborated in vivo using two murine models of pulmonary metastasis. The regulation of melanoma cell plasticity by VCAM-1 highlights the complex regulation of tumor-matrix interactions.Implications: Nanotechnology has revealed a novel dichotomic function of the VCAM-1/VLA-4 interaction on melanoma cell plasticity, as nanoscale tuning of this interaction reciprocally determines adhesion and spreading in a ligand density-dependent manner. Mol Cancer Res; 16(3); 528-42. ©2017 AACR.